2021
DOI: 10.1371/journal.pone.0254899
|View full text |Cite
|
Sign up to set email alerts
|

Relevant factors of self-care in children and adolescents with spastic cerebral palsy

Abstract: Objective Manual ability is considered one of the factors that can predict functional independence in activities of daily living. For evaluating personal tasks such as self-care, the Pediatric Evaluation of Disability Inventory (PEDI) comprises/introduces/offers a set of useful measures that assist in enhancing the capability for self-care among children and adolescents with cerebral palsy (CP). The aim of this study was to investigate the relevant factors of self-care capability and performance in children an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, added to the assessment of grasping and manual dexterity, it involves visual-motor coordination, a function that can also be affected in children with CP. The BBT has shown a significant correlation with the performance of children with CP evaluated with the PEDI [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, added to the assessment of grasping and manual dexterity, it involves visual-motor coordination, a function that can also be affected in children with CP. The BBT has shown a significant correlation with the performance of children with CP evaluated with the PEDI [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Looking at the research focus, the ICF component of activities, part of the AP component, was the most frequent area of interest in studies. These studies used tools or methods of assessment to analyze AYA capacities or performance in activities such as mobility [ 48 ], hand use [ 49 ], and activities of daily life [ 50 ]. Functional classification systems such as GMFCS, MACS, and CFCS are frequently used to categorize AYA capacity level or to analyze the relationship between the capacity level and other variables.…”
Section: Discussionmentioning
confidence: 99%
“…Motor issues in CP tend to affect trunk control and upper limb function, but their relationship has been studied principally in children and young people with CP [2,3]. Kusumoto et al [4] reported that better trunk control and, therefore, greater proximal stabilisation could improve upper limb function, suggesting a positive impact on self-care tasks in children and adolescents with spastic CP. However, little is known about this relationship in adulthood.…”
Section: Introductionmentioning
confidence: 99%